User acceptance of automated shuttles in Berlin-Schöneberg: A questionnaire study. (October 2018) - Nordhoff, Sina; de Winter, Joost; Madigan, Ruth; Merat, Natasha; van Arem, Bart; Happee, Riender
Highlights: The opinions of 384 users of an automated shuttle were examined via a survey. Respondents were overall positive about the shuttle. Respondents were less satisfied with the shuttle's speed and luggage space. Abstract: Automated shuttles are now in a prototyping phase in several research projects. However, there is still a paucity of knowledge on the acceptance of these shuttles. This paper presents the results of a questionnaire study among individuals ( n  = 384) who physically experienced an automated shuttle on an office campus in Berlin-Schöneberg. The findings indicate that the respondents were positive towards automated shuttles and could envision their use as feeders to public transport systems, in both urban and rural areas. The respondents were less satisfied with the effectiveness of the shuttle compared to their existing form of travel, the speed of the shuttle, and the space for luggage. A principal component analysis resulted in the retention of three components: (1) intention to use, (2) shuttle and service characteristics, and (3) shuttle effectiveness compared to existing transport. Older respondents expressed a higher intention to use, but found the shuttle less effective than their existing travel. We argue that automated shuttles are a valued concept, but speed and efficiency have to improve, in order for automated shuttles to become viable on a wide scale. Future research should use more objective measures and establish long-term effects in larger, more representative samples.